On the Number of Sections in the Auslander-Reiten Quiver of Algebras of Dynkin Type (2017)
ABSTRACT: Categorification of integer sequences A083329, A000295 and A049611 in the OEIS is given by using the number of sections in the Auslander-Reiten quiver of path algebras of type kΔ, where Δ is an oriented Dynkin diagram of type 6 7 An, Dn, E , E and . E8 In particular, the sequence A000295 counts the number of Dyck paths of semilength n having exactly one long ascent.